Reaffirmation of accreditation - Mary Ellen Petrisko::::::
In taking this action to reaffirm accreditation, the Commission confirms that CSUCI has satisfactorily addressed the Core Commitment....[and] has successfully completed the multistage review conducted under the 2013 Standards of Accreditation.